The Role of Job Embeddedness and Organizational Continuance Commitment on Intention to Stay: Development of Research Framework and Hypotheses - Zainuddin, Yuserrie; Noor, Ayesha (KnE Social Sciences, 2019)
The purpose of this paper is to develop a research framework and hypotheses based on a thorough review of the conceptual and empirical research in organizational behavior literature. Previous research has shown that there is an important relationship between on-the-job, off-the-job embeddedness, organizational continuance commitment, and employee’s intention to stay. Organizational continuance commitment is hypothesized to have a mediating effect on the relationship between on-the-job, off-the-job, and intention to stay. Implications for testing these hypotheses are articulated from research and practice perspectives. Research framework from this paper will be used at the preliminary stage of the research on ICT industry that can be expected to contribute to the development of ICT workers in Malaysia.